The implementation of community-based programs in Vietnam is promising in promoting health - Pardoel, Zinzi E.; Reijneveld, Sijmen A.; Lensink, Robert; Postma, Maarten; Thuy, Tran B.; Viet, Nga C.; Phuong, Lien N. T.; Koot, Jaap A. R.; Landsman, Jeanet J. A. (Frontiers in Public Health, 2023)
Background Low-and middle-income countries mostly have ageing populations with many unmet economic, social, or health-related needs, Vietnam being an example. Community-based support in Vietnam, organized as Intergenerational Self-Help Clubs (ISHCs) based on the Older People Associations (OPA) model, can help to meet these needs by the provision of services for various aspects of life. This study aims to assess the implementation of the ISHCs and whether successful implementation is associated with more member-reported positive health. Methods We used the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to evaluate the implementation using multiple data sources: ISHC board surveys (n = 97), ISHC member surveys (n = 5,080 in 2019 and n = 5,555 in 2020), focus group discussions (6; n = 44), and interviews with members and board leaders (n = 4). Results Reach ranged between 46 and 83% of ISHCs reaching target groups, with a majority of women and older people participating. Regarding Effectiveness, members indicated high satisfaction with the ISHCs. Adoption scores were high, with 74%–99% for healthcare and community support activities, and in 2019, higher adoption scores were associated with more members reporting good positive health. In 2020, reported positive health slightly decreased, probably due to the influence of the COVID-19 pandemic. A total of 61 ISHCs had consistent or improving Implementation from 2019 to 2020, and confidence in Maintenance was high. Conclusion The implementation of the OPA model in Vietnam is promising regarding its promotion of health and may help to tackle the needs of an ageing population. This study further shows that the RE-AIM framework helps to assess community health promotion approaches.